ABOUT BEAUTY IN RELIGIOUS TEACHINGS - Shakhnoza Tursunkulova (Web of Journals Publishing, 2024)
The article discusses the teachings of Sufism, that is, mystical beauty and its various aspects are analyzed. Opinions on mystical beauty and the philosophical aspects of the concept of beauty are set out in various religious sources.
Keywords: Sufism, religion, beauty, Zoroastrianism, Islamic teaching, hadith.